Verification of Photon Beam Absorbed Dose Using the Tissue Phantom Ratio Parameter on the Linac Clinac Cx at Andalas University Hospital - Nisa Nisa Oktania; Dian Milvita; Rico Adrial; Fiqi Diyona (Jurnal Fisika Unand, 2026)
Research on verification of the radiation dose of a 6 MV and 10 MV photon beam on Clinac CX type Linear Accelerator (LINAC) has been conducted at Andalas University Hospital. This research aims to determine the radiation beam correction factor to obtain measured dose values and obtain the value of absorbed dose verification value based on the Technical Report Series (TRS) No. 398 International Atomic Energy Agency (IAEA). The research began with planning on the CT-simulator. Furthermore, the measurement of radiation dose on the phantom slab using a Clinac CX type LINAC therapy aircraft with a farmer chamber ionization detector, target depth variations of 1,5 cm, 2,5 cm, and 10 cm, and field area variations of (6×6) cm2, (10×10) cm2, (15×15) cm2, (8×13,3) cm2, dan (9×11,5) cm2. Furthermore, radiation dose verification is carried out by comparing the radiation dose at the TPS to the dose measured using the farmer chamber ionization detector. The absorbed dose value obtained based on the planning dose at the TPS increased at maximum depth and decreased as the depth of the irradiation field increased. Verification of the radiation dose that meets the tolerance limit is below 5%. The appropriate measurement results were obtained at a maximum depth (Dmax) of 2,5 cm, except at depths of 1,5 cm and 10 cm.